Development and validation of a financially affordable Islamic home financing model in Malaysia - Mohd Zaidi Md Zabri (IIUM Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2018)
Home is a basic need. Yet it is becoming increasingly difficult for many Malaysians, particularly the low- and middle-income households to afford to buy a house. Studies have shown that the lack of financial affordability is largely due to the existing debt-based financing model and they have recommended the use of equity-based home financing model to be offered by financial cooperatives. Hence, this study developed and validated an integrated Cash Waqf-Financial Cooperative-Musharakah Mutanaqisah (CWFCMM) Model that could be used to provide financially affordable Islamic home financing in Malaysia. The study used mixed methods of interviews and questionnaire surveys. The interviews were conducted with 10 expert informants to validate the CWFCMM Model. The questionnaires, developed based on the extended Theory of Planned Behaviour (TPB), were distributed to 417 respondents, out of which 382 were usable. The interview data were analysed using thematic analysis while the data from the questionnaire survey were analysed using the Structural Equation Modelling (SEM). Expert informants unanimously agree that the Model is a viable alternative for financially affordable Islamic home financing model in Malaysia. Similarly, the findings from the quantitative survey data are also positive and promising. The study hypothesised that the Behavioural Intention of potential homeowners to participate in the CWFCMM Model is influenced by Attitude, Subjective Norm, Perceived Behavioural Control, and Perceived Cost Advantages. The study finds that: (1) when a potential homeowner has a favourable attitude towards the CWFCMM Model, he/she is more likely to be a participant; (2) if a potential homeowner believes that he/she has a greater autonomy over factors that might impede or facilitate their participation, the stronger his/her intention to participate in the CWFCMM Model; and (3) a positive perception towards the cost advantages of CWFCMM Model will influence a potential homeowner's decision-making process of CWFCMM Model participation in the future. This study contributes to the development of cash waqf institutions and financial cooperatives to enhance their capacity and capability, and a more targeted approach in marketing and promotion to improve the overall attitude and (existing and potential) donors' perception on cash waqf. The study also adds stock to the current literature especially in terms of the additional item of Perceived Cost Advantages and application of TPB in a new setting of third sector economic institutions in Malaysia.